Prevalence of Rejection of Skin Grafts in Type 2 Diabetic Patients with Deep Burns. A Comparative Cross Sectional Study - Mufassar Nishat, Sehar Khowaja, Mashal Siddiqui, Muhammad Ali Qureshi, Abdul Rashid Baloch (Pakistan Journal of Medical & Health Sciences, 2022)
The aims and objectives of current study were to provide best surgical services to diabetic burn patients by identifying their after skin graft complications. Focus was essential on the process of burn treatment with an emphasis on early excision and grafting. The frequency percentage mean standard deviation of percentage of burn, random diabetes levels, burn grade, burn surface area and TBSA in Group A (2.5 ± 1.6,10 ± 1.4, 1 ± 1.0, 4 ± 2.1, 2 ± 1.6) and Group B(4.1 ± 2.4, 16 ± 2.7, 1.6 ± 1.5, 6 ± 3.1, 4 ± 1.8) were calculated respectively. Similarly the rejection of skin grafts mean standard percentage deviation of diabetic and non-diabetic patients were (32.12 ± 11.12), (15.10 ± 12.15). The results of this study were highly significant (<0.005) and remarkable complicational changes were noted in the variables of diabetic than non-diabetic patients.